Identifying the Assessment Principles for the Tax Potential of the Industrial Enterprises in the Region - Klius, Yuliia; Ivchenko, Yevhen; Morhachov, Illia; Manukhina, Marta; Serikova, Olha; Hussein Ibrahim, Mohamed Saad (European Journal of Sustainable Development, 2021)
A special place in the industrial enterprise’s financial relations belongs to the relationship with the State budget and the earmarked budgetary and non-budgetary funds regarding the tax and fees charges and payments. These relationships arise from the moment the enterprise was created and continue throughout the entire period of its operation. Determining the amount of taxes and fees that an enterprise should pay based on the results of its activities, ensuring the timeliness and completeness of tax calculations, forming tax potential, assessing it and optimizing the tax burden (tax planning) are important areas of work for the financial services of an industrial enterprise.